Fuzzy object blending in 2-D - Çinar, A; Arslan, A (Springer-Verlag Berlin, 2001)
In this paper, a new curve modeling method using fuzzy logic is presented for blending in 2-D. For this goal, approximation curves are produced by means of fuzzy logic techniques. The base of the study is to obtain least three internal points of the curve by fuzzy logic, in case of knowing the start and end control points. After internal points are obtained, all points including start and end points of the approximation curve are created. As application, the method is applied to blending process and some sample blended objects are given in 2-D.
International Conference on Computational Science (ICCS 2001) -- MAY 28-30, 2001 -- San Francisco, CA
Keywords: Fuzzy logic technique; object blending and curve modeling